1996
DOI: 10.1111/j.1525-1446.1996.tb00220.x
|View full text |Cite
|
Sign up to set email alerts
|

Older Adults' Experience of Health Promotion: A Theory for Nursing Practice

Abstract: Understanding older adults' experience of health promotion is essential in effectively preserving health and functional ability and thereby reducing health care costs among members of this rapidly expanding group. During 5 months of participant observation of 80 older adults (ages of 62-88), data from 31 semistructured interviews, as well as the Health Self-Determinism Index (HSDI) designed to measure intrinsic motivation for health (Cox, Miller, & Mull, 1987), were analyzed using methods common to grounded th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
17
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 17 publications
3
17
0
Order By: Relevance
“…We conceptualize health status as how individuals view their own health (Zabalegui, 1994). We recognize that older adults are generally thought to have the tendency to define their health in terms of their ability to function both independently and effectively, irrespective of the presence of diseases (Frenn, 1996;Kaufmann, 1996).…”
Section: Operational Definitionsmentioning
confidence: 99%
“…We conceptualize health status as how individuals view their own health (Zabalegui, 1994). We recognize that older adults are generally thought to have the tendency to define their health in terms of their ability to function both independently and effectively, irrespective of the presence of diseases (Frenn, 1996;Kaufmann, 1996).…”
Section: Operational Definitionsmentioning
confidence: 99%
“…In studies utilizing the grounded theory approach, the discovered grounded theory is generally called a theory ( Chen, 1996; Frenn, 1996) or a model ( Wilde et al , 1994 ; Kyngäs & Hentinen, 1995; Backman & Hentinen, 1997). In the scientific sense, a model may be used to define or describe something and to specify relationships and processes, while a theory is a systematically related set of statements, including law‐like generations, which is empirically testable ( Lancaster & Lancaster, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Zauszniewski (1996b) found that elders who used both self-help and help-seeking strategies reported better psychological well-being and physical functioning than elders who did not use self-help and help-seeking strategies or elders who used only one of these types of strategies. Yet, the effects of social cognitive factors such as enabling skills (i.e., learned resourcefulness) and internal motivation for health (health self-determinism) on elders' use of self-help or help-seeking skills remain unknown (Frenn, 1996;Rosenbaum, 1990). Norman and Conner (1995) have proposed that five stages are required in an integrative social cognitive model for predicting health: precontemplative, contemplative, motivation, initiation, and maintenance (see Figure 1).…”
mentioning
confidence: 99%
“…This stage involves intrinsic processes (health selfdeterminism) that one uses in mobilizing internal resources (i.e., learned resourcefulness) for performing self-care activities or seeking help from formal or informal sources (Norman & Conner, 1995). Health self-determinism may play a key role in moderating the relationship between learned resourcefulness and help responses (Braden, 1990;Frenn, 1996). The initiation stage involves the performance of activities directed toward health promotion (Norman & Connor, 1995), such as the three help responses: selfhelp, informal help seeking, and formal help seeking.…”
mentioning
confidence: 99%
See 1 more Smart Citation